Endurance of SN 2005ip after a decade: X-rays, radio and Hα like SN 1988Z require long-lived pre-supernova mass-loss. Issue 3 (10th December 2016) - Smith, Nathan; Kilpatrick, Charles D.; Mauerhan, Jon C.; Andrews, Jennifer E.; Margutti, Raffaella; Fong, Wen-Fai; Graham, Melissa L.; Zheng, WeiKang; Kelly, Patrick L.; Filippenko, Alexei V.; Fox, Ori D.
Abstract: Supernova (SN) 2005ip was a Type IIn event notable for its sustained strong interaction with circumstellar material (CSM), coronal emission lines and infrared (IR) excess, interpreted as shock interaction with the very dense and clumpy wind of an extreme red supergiant. We present a series of late-time spectra of SN 2005ip and a first radio detection of this SN, plus late-time X-rays, all of which indicate that its CSM interaction is still strong a decade post-explosion. We also present and discuss new spectra of geriatric SNe with continued CSM interaction: SN 1988Z, SN 1993J and SN 1998S. From 3 to 10 yr post-explosion, SN 2005ip's Hα luminosity and other observed characteristics were nearly identical to those of the radio-luminous SN 1988Z, and much more luminous than SNe 1993J and 1998S. At 10 yr after explosion, SN 2005ip showed a drop in Hα luminosity, followed by a quick resurgence over several months. We interpret this Hα variability as ejecta crashing into a dense shell located ≲ 0.05 pc from the star, which may be the same shell that caused the IR echo at earlier epochs. The extreme Hα luminosities in SN 2005ip and SN 1988Z are still dominated by the forward shock at 10 yr post-explosion, whereas SN 1993J and SN 1998S are dominated by the reverse shock at a similar age. Continuous strong CSM interaction in SNe 2005ip and 1988Z is indicative of enhanced mass-loss for ∼10 3  yr before core collapse, longer than Ne, O or Si burning phases. Instead, the episodic mass-loss must extend back through C burning and perhaps even part of He burning.